2016
DOI: 10.2355/isijinternational.isijint-2016-256
|View full text |Cite
|
Sign up to set email alerts
|

Internal Stress and Elastic Strain Energy in Pearlite and Their Accommodation by Misfit Dislocations

Abstract: Internal stress and elastic strain energy in pearlite caused by misfit between ferrite and lamellar cementite were theoretically analyzed based on micromechanics while taking into account an accommodation mechanism of the misfit strain between ferrite and cementite on pearlitic transformation. Two-dimensional large deformation analysis reveals that the Pitsch-Petch orientation relationship is most appropriate among already reported crystal orientation relationships under the condition that the interface contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…26) Thus, authors proposed that the internal stress generated by the misfit between ferrite and cementite has large influence on the strength of pearlite steels. [26][27][28][29][30][31] Figure 12 shows X-ray (211) ferrite diffraction peak containing Kα1 and Kα2 of 40C0Mn and 100C2Mn with IF steel as a reference. As shown above in Table 2, 40C0Mn and 100C2Mn have the lowest and highest 0.2% proof stress, respectively.…”
Section: Strength Mechanism Of Pearlite By Mn Additionmentioning
confidence: 99%
“…26) Thus, authors proposed that the internal stress generated by the misfit between ferrite and cementite has large influence on the strength of pearlite steels. [26][27][28][29][30][31] Figure 12 shows X-ray (211) ferrite diffraction peak containing Kα1 and Kα2 of 40C0Mn and 100C2Mn with IF steel as a reference. As shown above in Table 2, 40C0Mn and 100C2Mn have the lowest and highest 0.2% proof stress, respectively.…”
Section: Strength Mechanism Of Pearlite By Mn Additionmentioning
confidence: 99%
“…Recently, Nakada and Kato have evaluated such interface stress generation and its relaxation by introduction of misfit dislocations using a micro-mechanics model. 29)…”
Section: Pearlite Transformation and Change In Ferritementioning
confidence: 99%
“…Nakada and Kato estimated the elastic strain due to the misfit between ferrite and cementite by a calculation using micromechanics. 27) They suggested that the elastic strain energy changes according to the crystal orientation relationship and the lattice parameter gap due to distribution of alloying elements between the two phases. 28) To consider the effect of V distribution on the lattice strain, we attempted to evaluated the principal strain and elastic strain energy of the misfit based on the literature data.…”
mentioning
confidence: 99%
“…28) To consider the effect of V distribution on the lattice strain, we attempted to evaluated the principal strain and elastic strain energy of the misfit based on the literature data. 27) The lattice parameter data of cementite (Fe 3 C) and its alloyed counterparts, which were studied by Razumovskiy and Ghosh using first-principles calculation, 29) were referred. Here, the cementite lattice parameters are a θ , b θ , and c θ , in ascending order.…”
mentioning
confidence: 99%